1993
DOI: 10.1126/science.259.5101.1599
|View full text |Cite
|
Sign up to set email alerts
|

Fullerenes from a Fulgurite

Abstract: Peaks at 720 and 840 atomic mass units were identified by mass spectrometry in a sample extracted from a fulgurite, which is a glassy rock that forms where lightning strikes the ground. The peaks are interpreted as arising from C(60) and C(70) and the associated peaks as produced from other fullerenes. The intense conditions generated by the lightning not only melted the rock it struck and fused the associated soil but also allowed fullerenes to form, presumably from the organic debris in the soil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(39 citation statements)
references
References 24 publications
0
38
1
Order By: Relevance
“…On Earth, fullerenes, primarily C 60 and C 70 , have been extracted from two Cretaceous-Tertiary boundary sites in New Zealand and may be the result of extensive wildfires [39]. They have also been found in fulgurite, a glassy rock that forms when lightning strikes the ground [40], in coal samples found in China [41,42], and in shungite, a carbon-rich Precambrian rock from Karelia, Russia [43]. Fullerenes were also found in residue from the Allende meteorite [44] and the 1.85-billion-year-old Sudbury meteorite impact structure in Ontario, Canada [45].…”
Section: Formation Offullerenes and Nanostructuresmentioning
confidence: 99%
“…On Earth, fullerenes, primarily C 60 and C 70 , have been extracted from two Cretaceous-Tertiary boundary sites in New Zealand and may be the result of extensive wildfires [39]. They have also been found in fulgurite, a glassy rock that forms when lightning strikes the ground [40], in coal samples found in China [41,42], and in shungite, a carbon-rich Precambrian rock from Karelia, Russia [43]. Fullerenes were also found in residue from the Allende meteorite [44] and the 1.85-billion-year-old Sudbury meteorite impact structure in Ontario, Canada [45].…”
Section: Formation Offullerenes and Nanostructuresmentioning
confidence: 99%
“…Finding anatase within the fulgurite specimen provides further evidence to suggest that the temperature of the glass formation was lower in some regions within the sample than the reported 1800 • C attained, when lightning hits the surface of sand or a rock (Uman 1964;Krider & Dawson 1968). Daly et al (1993) previously reported fullerenes in a fulgurite, though the pathway of fullerenes production could not be definitively linked to the fulgurite formation process (Heymann et al 2003). Graphite has also been observed in fulgurite glasses, presumably resulting from the reduction of organic compounds in the precursor soil (Essene & Fisher 1986).…”
Section: Resultsmentioning
confidence: 94%
“…Rather, alternative ways should be explored as to how these unusual mineral assemblages may have formed. We suggest that they may be the products of lightning strikes (Essene and Fisher, 1986;Daly et al, 1993). Novel ultra-high temperature experiments at >6000 K reported here show that ultra-reduced phases can precipitate directly from plasmas.…”
Section: Introductionmentioning
confidence: 89%